Head-to-head comparison of V-A ECMO, Impella and ECPELLA in normal ovine hearts - Konstantin Yastrebov; Hugh S. Paterson; David H. Tian; Laurencie M. Brunel; Fiona C. Schnitzler; Lisa M. Partel; Mark Dennis; Paul G. Bannon (Scientific Reports)
Abstract Temporary mechanical circulatory support (MCS), including veno-arterial extracorporeal membrane oxygenation (ECMO) and micro-axial pumps (Impella), is increasingly used in clinical practice for refractory circulatory failure. Complex physiological responses to each technique or their combination (ECPELLA) remain debated and are often specific to cardiovascular pathology. A paucity of data on physiological responses to MCS in normal subjects makes comprehensive understanding of such responses in variable disease states difficult, as well as during weaning MCS in recovering hearts. This translational investigation compared three MCS techniques with variable pump flows in healthy sheep (n = 7) to establish baseline for future studies in cardiomyopathic models. All MCS techniques increased arterial elastance, but reduced LV myocardial work, coronary arterial flow and LV myocardial oxygen consumption. ECPELLA was more effective in increasing total systemic blood flow and MAP. The overall similarity between the MCS techniques suggests that the more invasive and complex combination of devices (ECPELLA) can only be justified for management of the severe failing heart as the means for decompressing LV. A study investigating the comparative impacts of different regimes and MCS techniques in a cardiomyopathic model is warranted.